2016
DOI: 10.1016/j.blre.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow and mass transfer regulation of coagulation

Abstract: Blood flow regulates coagulation and fibrin formation by controlling the transport, or mass transfer, of zymogens, co-factors, enzymes, and inhibitors to, from, and within a growing thrombus. The rate of mass transfer of these solutes relative to their consumption or production by coagulation reactions determines, in part, the rate of thrombin generation, fibrin deposition, and thrombi growth. Experimental studies on the influence of blood flow on specific coagulation reactions are reviewed here, along with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 73 publications
2
43
0
1
Order By: Relevance
“…41 Differences in fibrin surface coverage and thrombus size are most pronounced at venous and moderate arterial shear rates because there is less dilution of coagulation products by blood flow. 62 Similar observations of diminished thrombus volume were reported on type I collagen using thrombin inhibitors and hemophilia A samples. 67 The T-TAS® system was used to evaluate thrombus formation on collagen-TF surfaces in blood from a FVIII −/− mouse and with human blood treated with an anti-FIXa aptamer.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…41 Differences in fibrin surface coverage and thrombus size are most pronounced at venous and moderate arterial shear rates because there is less dilution of coagulation products by blood flow. 62 Similar observations of diminished thrombus volume were reported on type I collagen using thrombin inhibitors and hemophilia A samples. 67 The T-TAS® system was used to evaluate thrombus formation on collagen-TF surfaces in blood from a FVIII −/− mouse and with human blood treated with an anti-FIXa aptamer.…”
Section: Introductionsupporting
confidence: 72%
“…61 Despite these challenges, the motivation for measuring thrombus formation in hemophilia blood under flow stems from the well-documented regulation of coagulation by blood flow and the role of fibrin in establishing the mechanical properties of thrombi. 6264 …”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of platelet adhesion and aggregation and the relative role of platelet function and coagulation are regulated by forces and mass transfer limitations imposed on a growing thrombus by blood flow. 10,35 …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that individual reactions within the coagulation cascade can switch from being reaction-to transport-limited depending on the local conditions 69 . Limited transport increases the residence time of solutes in the platelet mass, which translates into reduced generation of new thrombin, and at the same time increased biological activity of locally trapped thrombin.…”
Section: Influence Of Local Hemodynamicsmentioning
confidence: 99%